2015
DOI: 10.1111/jgh.12721
|View full text |Cite
|
Sign up to set email alerts
|

Comparative portal hypotensive effects as propranolol of vitamin D3 treatment by decreasing intrahepatic resistance in cirrhotic rats

Abstract: Chronic vitamin D₃ treatment alone results in comparative portal hypotensive effects as propranolol alone in cirrhotic rats with PH. Taken together, chronic vitamin D₃ administration was an ideal alternative strategy to effectively improve PH without unwanted systemic side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…This observation could explain the findings of our in vivo experiments in animals treated with CAL and PCT, which exhibited a decreased spleen/body weight ratio as an indirect marker of portal hypertension. This finding is in accordance with that of a study by Lee et al [27], who described a comparable magnitude of reduction in portal hypertension by CAL and propranolol. Interestingly, the authors of that study identified a reduction in intrahepatic resistance (IHR) as one mechanism of action, in addition to a reduction in fibrosis [27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This observation could explain the findings of our in vivo experiments in animals treated with CAL and PCT, which exhibited a decreased spleen/body weight ratio as an indirect marker of portal hypertension. This finding is in accordance with that of a study by Lee et al [27], who described a comparable magnitude of reduction in portal hypertension by CAL and propranolol. Interestingly, the authors of that study identified a reduction in intrahepatic resistance (IHR) as one mechanism of action, in addition to a reduction in fibrosis [27].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with that of a study by Lee et al [27], who described a comparable magnitude of reduction in portal hypertension by CAL and propranolol. Interestingly, the authors of that study identified a reduction in intrahepatic resistance (IHR) as one mechanism of action, in addition to a reduction in fibrosis [27]. Among several other mechanisms causing a reduction in IHR, a reduction in angiotensin II-induced HSC contractility by CAL was identified [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[ 49,50 ] Vitamin D treatment for 10 weeks reduced portal pressure in cirrhotic rats by decreasing intrahepatic resistance. [ 51 ] In this study, we focused on intestine but not hepatic status. Different from the previous study which initiated vitamin D treatment immediately after the first administration of TAA, [ 51 ] we started calcitriol intervention in ascites‐developed cirrhotic rats after TAA injection for 16 weeks in order to investigate the potential effects of calcitriol on bacterial translocation, which was commonly observed in ascitic rats.…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ] In this study, we focused on intestine but not hepatic status. Different from the previous study which initiated vitamin D treatment immediately after the first administration of TAA, [ 51 ] we started calcitriol intervention in ascites‐developed cirrhotic rats after TAA injection for 16 weeks in order to investigate the potential effects of calcitriol on bacterial translocation, which was commonly observed in ascitic rats. [ 52 ] Besides, hepatic improvement caused by long‐term calcitriol administration would also impact intestinal environment and function via liver–gut axis, [ 40 ] and interfere us to examine the direct effects of calcitriol on intestine.…”
Section: Discussionmentioning
confidence: 99%